Knowledge and perception of dental profession students about the selection of mouthwash for recurrent aphthous stomatitis (RAS) therapy - Ayuningtyas, Nurina Febriyanti; Surboyo, Meircurius Dwi Condro; Nagoro, Ayu Anggraini Broto; Hendrayanto, Shalma Maulidya; Rachmadanti, Zhafira Khansa (International Journal Labs, 2024)
Recurrent aphthous stomatitis (RAS) is a recurring ulcer on the oral mucosa with no known cause and without association with systemic diseases. Dental profession students are expected to have adequate knowledge and positive perceptions regarding the use of mouthwash for RAS therapy. This study aimed to describe the levels of knowledge and perception of dental students about the selection and use of mouthwash for managing RAS. The study involved 90 students from the Dental Profession Study Programme at the Faculty of Dental Medicine, Universitas Airlangga, Surabaya. Data were collected through an online questionnaire comprising 18 questions, divided into two categories: (1) knowledge of mouthwash brands, active ingredients, usage duration, and timing, and (2) perceptions regarding the importance, safety, and effectiveness of mouthwash for RAS. The responses were tabulated and presented in percentages. The results revealed that 95.56% of respondents demonstrated good knowledge of mouthwash for RAS therapy. Perceptions of the importance, safety, and effectiveness of mouthwash were 87.78%, 98.89%, and 94.44%, respectively, with an overall positive perception rate of 92.22%. In conclusion, dental profession students at Universitas Airlangga possess a high level of knowledge and positive perceptions about the use of mouthwash for RAS therapy.